Pengaruh Natrium Tripolyphosphate Terhadap Sifat Fisik Beton Cor Di Dalam Air (Under-Water Concrete) - Hasmiyati Hasmiyati; Ismeddiyanto Ismeddiyanto; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In the implemetation of concrete building construction there is a problem when casting in water. To solve this problem, sodium tripolyphosphate use in the concrete mixture. The purpose of using sodium tripolyphosphate is to accelerates the process of concrete hardening in water as well is to increase the binding of fresh concrete material. The alternative to maintain the quality concrete in water filler was needed. The filler used namely stone ash (self compacting concrete). The stone ash is hygroscopic and easy to obtain. The use of stone ash is to increase the viscosity of fresh concrete while reducing the tendency of segregation and bleeding in fresh concrete. The goal of the study is to determine Sodium Tripolyphosphate effect to the physical properties of under water concrete and to obtain the optimum composition of constituents of under water concrete. Sodium Tripolyphosphate which is used in this study is the addition of variations of 5%, 10% and 15% to the weight of cement. While the amount of stone ash used is 10% to the weight of fine aggregate. The slump flow of 5%, 10% and 15% sodium tripolyphosphate is 620 mm, 570 mm and 400 mm, respectively. The volume weight concrete with 5%, 10% and 15% sodium tripolyphosphate are 2274.98 kg/m3, 2312.54 kg/m3 and 2288.14 kg/m3, respectively. Whereas the porosity concrete with 5%, 10% and 15% sodium tripolyphosphate respectively were 23.10%, 21.97% and 22.55%. From the FTIR test results, it is showed that 10% sodium tripolyphosphate is the mixture were more stable compared to other variations.Key words: Sodium tripolyphosphate, under water concrete, stone ash, variation, percentage